Solidarity in Diversity? State Responses to Religious Diversity in Liberal and Non-Liberal Perspectives. Issue 7 (October 2019) - Neo, Jaclyn L.; Roßbach, Matthias; Thio, Li-ann; Tischbirek, Alexander
Abstract: This Article introduces the German Law Journal's Special Issue on "Solidarity in Diversity? State Responses to Religious Diversity in Liberal and Non-Liberal Perspectives". The major countries in comparative focus are Germany and Singapore, both self-avowedly secular countries that face the challenge of religious diversity: Singapore, from inception, and Germany, through more recent developments. A key issue the Article raises concerns liberal approaches towards regulating religion; it argues that the liberal model, taking Germany as an example, may serve as a productive starting point for comparative analysis, as the liberal focus on individual religious freedom impacts managing religious diversity, shapes national cultural identity, models of secularism and social solidarity. This is compared with non-liberal approaches, as exemplified in Singapore practice, where a more communitarian outlook underpin more interventionist approaches whereby public interests and the common good tend to be prioritized over individual freedom. The comparative angles offered in this Special Issue is furthermore buttressed in several articles in this Special Issue that make comparisons to other jurisdictions-United States and Canada. This introductory Article offers a brief overview to the various contributions to this Special Issue and identifies unifying themes.